Digital Nomads Interest and Satisfaction in Doing Workcations in Hotel at Greater Bandung Region: The AIDA+S Model Application - Azizah Salsabila Nugraha; Novi Nuryanti (Politeknik Negeri Bandung, 2022)
The pandemic that has hit the whole world has made the tourism industry suffer loses. Consumers are looking for safer tourism activities. Tourism business people are looking for solutions to this by creating a new adaptive tourism trend, which is the Work-Based Vacations (Workcations), an evaluation of the word “Bleisure”. A digital nomad who works as a freelancer is intrested in this trend. Using the AIDA+S (Attention, Interest, Desire, Action, Satisfaction) model, this research was conducted to determine the interest and satisfaction of digital nomads in the trend of Workcations in the Bandung Raya area’s hotel accomodations. This study uses a descriptive quantitative method with frequency analysis, cross=tabulation, and scoring analysis. Samples were taken using a stratified random sampling technique to 105 respondents. Respondents are digital nomads who worked as a freelancer and had carried out the Workcations trend in a hotel in the Bandung Raya Area during the new normal period and are aged 17 years old and over. The results of the research show that the interest and satisfaction of digital nomads are high on the trend of Workcations as an alternative tourism trend in the new normal period.